Monetary union and fiscal discipline evidence from the Caribbean - Lorde, Troy...[et al.] ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Examines fiscal policy in Caribbean countries that are members of a monetary union.